The Influence of Personal Branding and Social Media Marketing on Brand Image with Brand Awareness as an Intervening Variable - Akbar, Tiara Arayni; Nurjanah, Siti (SAN Scientific, 2023)
Every business actor must decide the correct approach to survive in a competitive market. This study examined Erika Richardo's personal branding and social media marketing on By Painters brand image, using brand awareness as an intervening variable. Quantitative research uses non-probability sampling with purposive sampling in this study. The data collection approach consists of sending surveys to 100 Instagram followers of